2019
DOI: 10.1186/s12885-019-5364-3
|View full text |Cite
|
Sign up to set email alerts
|

Insluin and epithelial growth factor (EGF) promote programmed death ligand 1(PD-L1) production and transport in colon cancer stem cells

Abstract: Background Programmed cell death ligand 1 (PD-L1) is an important immune-inhibitory protein expressed on cancer cells to mediate cancer escape through interaction with PD-1 expressed on activated T lymphocytes (T cells). Previously, we reported that colon and breast cancer stem cells (CSCs) expressed much higher levels of PD-L1 than their parental cells, suggesting they will be more resistant to immune attack. Methods We investigated the underlining mechanism of PD-L1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 48 publications
5
30
0
Order By: Relevance
“…TGFβ is considered as one of the most profibrotic cytokines and it is well established that TGFβ is a crucial modulator of ECM production in fibrogenic processes . As such, we first established that TGFβ upregulated PD‐L1 in both HuLFs and murine fibroblast cell lines (Figures and ); which extends previous work showing that PD‐L1 expression is upregulated by various cytokines, including IFN‐γ, GM‐CSF, IL‐17, TNF‐α, and EGF . To address whether PD‐L1 had a central role in profibrotic TGFβ signaling, PD‐L1 was knocked down with siRNA and the cellular response to TGFβ was examined.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…TGFβ is considered as one of the most profibrotic cytokines and it is well established that TGFβ is a crucial modulator of ECM production in fibrogenic processes . As such, we first established that TGFβ upregulated PD‐L1 in both HuLFs and murine fibroblast cell lines (Figures and ); which extends previous work showing that PD‐L1 expression is upregulated by various cytokines, including IFN‐γ, GM‐CSF, IL‐17, TNF‐α, and EGF . To address whether PD‐L1 had a central role in profibrotic TGFβ signaling, PD‐L1 was knocked down with siRNA and the cellular response to TGFβ was examined.…”
Section: Discussionsupporting
confidence: 70%
“…65 As such, we first established that TGFβ upregulated PD-L1 in both HuLFs and murine fibroblast cell lines (Figures 1 and 2); which extends previous work showing that PD-L1 expression is upregulated by various cytokines, including IFN-γ, GM-CSF, IL-17, TNF-α, and EGF. [66][67][68][69][70] To address whether PD-L1 had a central role in profibrotic TGFβ signaling, PD-L1 was knocked down with siRNA and the cellular response to TGFβ was examined. Inhibition of PD-L1 expression significantly reduced TGFβ induced profibrotic target genes, cell migration, and soft agar colony formation (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…For colon cancer HT-29 cells, we recently showed that after SP1 culturing, the clustered cells increased the expression of stem cell markers including CD133, CD24 and CD44. 26 Collectively, our data showed that after SP1 culturing, colon cancer cells have enriched cancer stemness. Therefore, upon subsequent culturing of the enriched cancer stemness of SP1 culture (ie SP2), spherical clusters with >20% population of single cells formed within 24 hours.…”
Section: Discussionmentioning
confidence: 66%
“…The synergy between EGF and insulin effects induced a remarkable increase in PD-L1 expression on the surfaces of CSCs. This elevated expression enhanced the ability of CSCs to form spheres [85]. The importance of proper glycosylation for maintaining PD-L1 stability was also emphasized by Cha et al [86].…”
Section: Other Mechanisms Of Aberrant Pd-l1 Expression In Human Tumorsmentioning
confidence: 88%
“…Inhibition of EGF by gefitinib affected PD-L1 levels by increasing its degradation [84]. Similarly, in colon cancer, Chen and coworkers found that EGF facilitated PD-L1 transport to the surface of cancer cells, which stabilized the protein [85]. They also found that insulin had a stimulatory effect on PD-L1 synthesis, which was mediated by activating the PI3k/ Akt pathway.…”
Section: Other Mechanisms Of Aberrant Pd-l1 Expression In Human Tumorsmentioning
confidence: 93%